CHANGES IN LAND USE / LAND COVER DUE TO POPULATION PRESSURE (WITH REFERENCE TO MADHYA PRADESH): जनसंख्या दबाव जनित भूमि उपयोग/भूिम आवरण में परिवर्तन (मध्यप्रदेश के संदर्भ में) - Gupta, Rekha (International Journal of Research -GRANTHAALAYAH, 2015)
There is an interdependent relationship between human and natural resources. By using his knowledge and skills on the biological and abiotic wealth derived from human nature, he converts them into valuable services and goods and gives direction and speed to economic development. Without human, this wealth of nature has no value. Human is both a means and a means of development. Pro. PL Rawat has said that man is both the beginning and the end of economic development, but when man starts exploiting or exploiting these natural wealth in order to fulfill his growing needs, the balance between man and nature starts to deteriorate and h ¨ Environmental problems also lead to birth. Today almost the entire world is facing a deteriorating balance of human and nature due to rapid growth. Our country and state are also not untouched by this problem. This imbalance can also be explained by population pressure in the state and changes in the nature of land use. मानव और प्राकृतिक संसाधनों में अन्योन्य आश्रित संबंध है। मानव प्रकृति से प्राप्त जैविक-अजैविक सम्पदा पर ही अपने ज्ञान एवं कौशल का उपयोग करके उन्हें बहुमूल्य सेवा एवं वस्तुओं में परिवर्तित करता है एवं आर्थिक विकास को दिशा एवं गति प्रदान करता है। मानव के बिना प्रकृति की इस सम्पदा का कोई मूल्य नहीं है। मानव ही विकास का साधन एवं साध्य दोनों है। प्रो. पी.एल. रावत ने कहा है कि, मनुष्य आर्थिक विकास का आदि एवं अंत दोनों है किन्तु जब मानव अपनी बढ़ती हुई आवश्यकताओं की पूर्ति के लिए इन प्राकृतिक संपद¨ का अत्यधिक शोषण या दोहन करने लगता है तो मानव व प्रकृति के बीच संतुलन बिगड़ने लगता है और ज¨ पर्यावरणीय समस्याओं के जन्म का कारण भी बनता है। आज लगभग संपूर्ण विश्व तीव्र वृद्धि के कारण मानव एवं प्रकृति के बिगड़ते संतुलन का सामना कर रहा है। हमारा देश एवं राज्य भी इस समस्या से अछूता नहीं है। इस असंतुलन को राज्य में जनसंख्या दबाव एवं भूमि उपयोग के स्वरूप में आए परिवर्तन के द्वारा भी स्पष्ट किया जा सकता हैं।